Consumptive Behavior in Online Shopping among Office Workers in Non-Metropolitan Areas - Hasnidar; Nila Ridayani; Jusri (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The development of e-commerce has changed people's consumption patterns, particularly in online fashion shopping activities, which increasingly encourages consumptive behavior. This study aims to analyze the influence of online shopping frequency, promotions and discounts, social media, and financial literacy on the consumptive behavior of office workers in Ujung Loe District, Bulukumba Regency. The study used a quantitative approach with a descriptive and associative design. Data were collected through an online questionnaire using Google Forms from 120 respondents selected using a purposive sampling technique. Data analysis was performed using multiple linear regression with the help of SPSS. The results of the study indicate that partially, online shopping frequency, promotions and discounts, and social media have a positive and significant influence on the consumer behavior of office workers. Meanwhile, financial literacy does not show a significant influence partially on consumer behavior. However, simultaneously, all four variables have a significant influence on consumer behavior, with a coefficient of determination of 61.20%. This finding indicates that office workers' consumer behavior in online fashion shopping is a multidimensional phenomenon influenced by external and internal factors. The novelty of this study lies in the focus on adult office workers and the context of non-metropolitan areas, which are still relatively limited in the study of online consumer behavior.